THE EFFECT OF HEALTH VALUE, SAFETY VALUE, AND ENVIRONMENTAL VALUE ON INTENTION TO PURCHASE ORGANIC PRODUCT: EMPIRICAL STUDY OF THE BODY SHOP COSMETICS - Berliana Widyaningrum; Imronudin Imronudin; Soepatini Soepatini (IAIN Surakarta, 2021)
This study aims to analyze the effect of health value, safety value, and environmental value on intention to purchase organic products (empirical study on the body shop cosmetics). The population of this research was the people of Surakarta knowing about the body shop products, and the research sample was 106 respondents. The type of data used in this study was primary data. Methods of collecting data applied a questionnaire. The analytical tool used to test the hypothesis used SmartPLS 3.0. The results show that the health value had no significant effect on the intention to buy organic products, while the safety and environmental values had a significant effect on the intention to buy organic products.